Sesamin Activates Nrf2/Cnc-Dependent Transcription in the Absence of Oxidative Stress in Drosophila Adult Brains - Tuan Dat Le; Yoshihiro H. Inoue (MDPI AG, 2021)
Sesamin, a major lignin in sesame seeds, possesses health-promoting properties. Sesamin feeding suppresses several aging-related phenotypes such as age-dependent accumulation of damaged proteins in the muscles and neuronal loss in the brains of Drosophila adults with high levels of reactive oxygen species. Sesamin promotes the transcription of several genes that are responsible for oxidative stress, although the underlying mechanism remains unclear. Here, we aimed to demonstrate that sesamin mediates its action through activation of a transcription factor, Nrf2 (Cnc in Drosophila), essential for anti-aging oxidative stress response. Nrf2/Cnc activation was determined using the antioxidant response element, Green Fluorescence Protein reporter, that can monitor Nrf2/Cnc-dependent transcription. We observed strong fluorescence in the entire bodies, particularly in the abdomens and brains, of adult flies fed sesamin. Interestingly, Nrf2/Cnc was strongly activated in neuronal cells, especially in several neuron types, including glutamatergic and cholinergic, and some dopaminergic and/or serotonergic neurons but not in GABAergic neurons or the mushroom bodies of flies fed sesamin. These results indicate that the anti-aging effects of sesamin are exerted via activation of Nrf2/Cnc-dependent transcription to circumvent oxidative stress accumulation in several types of neurons of adult brains. Sesamin could be explored as a potential dietary supplement for preventing neurodegeneration associated with accumulation of oxidative stress.